The recovery from COVID-19: pathophysiology and potential role of pulmonary rehabilitation program - Pádua, Karina Lúcia Cabral; Rosa, Karissa Yasmim Araújo; Oliveira, Miriã Cândida de; Lino, Maria Eduarda Moreira; Fonseca, Adriano Luís; Maldaner, Vinícius Zacarias; Melo, Felipe Xavier de; Santos, Dante Brasil (Manual Therapy, Posturology & Rehabilitation Journal, 2021)
The actual stage of SARS-CoV-2 pandemic reveals the necessity to rehabilitate patients, mainly those who were severe and critical ill during acute infection. These post-COVID19 patients might present multiple factors, which culminates in impairment of oxygenation to skeletal muscles, with prejudice in overall functional capacity. These factors can be described as a reduced pulmonary diffusion capacity, a cardiovascular and oxygen transport dysfunction and deconditioning of skeletal muscles. The proposition of pulmonary rehabilitation program for the aforementioned patients evaluates pulmonary, cardiac, skeletal muscles and overall function. The conduction of this program might address specifically each one of the potential impairment oxygenation factors, with significant impact evaluated functions and, by consequence, in overall functional capacity.